Autonomous control of hybrid AC-DC microgrids - Chai, Yi Kang (2012)
Modern renewable sources are by nature either AC or DC. As a result, future microgrids can be structured as hybrid networks with both AC and DC sub-grids in co-existence for improved efficiency, in contrast to the conventional AC grid. Recognising the importance of the control of power electronic converters in hybrid microgrids, this project investigated the droop control schemes of the elements in hybrid AC-DC microgrids. The droop control discussed in this project involved no communication link. All information was transferred through AC and DC voltages by varying and sensing of the frequency and amplitude of the AC and DC voltages. Control schemes of distributed generation, AC-DC interlinking converter and distributed storage were formulated and are included in this report. For distributed generation, the sources can share the AC and DC loads according to the coordination by the interlinking converter. As for distributed storage, the charging and discharging power can be determined by the overall loading of the microgrid according to the droop lines. In order to verify the control schemes, experiments were conducted. Through the sequences of events emulated in the experiments, the results have verified the proper operation of the droop control schemes discussed in this report.